SYSTEMATICS LITERATURE REVIEW: EFEKTIVITAS WORKED EXAMPLE DALAM PEMBELAJARAN MATEMATIKA - Azizah, Nur; Prihandhika, Aditya (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This study aims to determine the effectiveness of worked examples in mathematics learning and its impact on improving students' learning abilities in mathematics learning. The method used in this research is Systematic Literature Reviews (SLR). Identifying, selecting and determining selected articles from the database followed the PRISMA flow diagram with the established inclusion criteria. Of the 12 articles selected in this study, learning with worked examples was effective in 11 research articles, while 1 other article reported it was ineffective. In addition, worked examples have a positive impact in mathematics learning and have been proven effective in improving learning achievement, understanding, problem solving, proportional reasoning, representation and learning independence in mathematics learning.